2011
DOI: 10.1007/s00280-011-1601-4
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab plus gemcitabine and oxaliplatin as first-line therapy for metastatic or locally advanced pancreatic cancer: a phase II trial

Abstract: The GEMOX/bevacizumab regimen demonstrated an excellent median overall survival but did not meet our objective of a 14 month median survival. Toxicity was significant. We do not recommend further evaluation of this regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
16
0
3
Order By: Relevance
“…16,17,19,20 Trials were conducted between 2004 and 2008 and all included patients with APCA. All studies included bevacizumab at an equivalent dose of 5 mg/kg/wk in combination with a gemcitabine doublet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17,19,20 Trials were conducted between 2004 and 2008 and all included patients with APCA. All studies included bevacizumab at an equivalent dose of 5 mg/kg/wk in combination with a gemcitabine doublet.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 studies, the doublet contained a fluoropyrimidine, 16,20 and in 2 studies the doublet contained a platinum. 17,19 Only 2 of these trials met their primary endpoint. Median age and CA19-9 were similar among studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These regimens included: cisplatin and gemcitabine [46]; capecitabine and gemcitabine [47]; capecitabine, radiation, and gemcitabine [48]; oxaliplatin and gemcitabine [49]; gemcitabine and radiation [50, 51], and docetaxel [52] (Table 1). However, results from the Phase III trial directly comparing bevacizumab plus gemcitabine to placebo plus gemcitabine in advanced PDAC patients showed that the addition of bevacizumab does not result in an improvement in overall survival (OS) or progression free survival (PFS) or differences in the ORR (Table 3) [53].…”
Section: Clinical Studies In Pdacmentioning
confidence: 99%
“…Trials involving bevacizumab as a second-line therapy option have also failed to show much promise 48, 49 . More recently, bevacizumab has been tested in combination with gemcitabine and other chemotherapies and radiation therapies in adjuvant settings and has continued to show no success 50-52 .…”
Section: Current Monoclonal Antibody Therapies For Pda Treatmentmentioning
confidence: 99%